Analysis Of Optical And Electrical Properties Of Thin Films Ba1-xSrxTiO3 (With x = 0.1 and x = 0.6) - Zulkarnain, TS Luqman Husain, Rahmi Dewi, Krisman, Zuhdi (International Journal of Advanced Science and Technology, 2020)
Ferroelectric material which is currently being developed is Barium Strontium Titanat  (Ba1-xSrxTiO3). Ba1-xSrxTiO3 thin film is a thin layer semiconductor that can be applied as a capacitor. The method used in making Ba0.9Sr0.1TiO3 and Ba0.4Sr0.6TiO3 thin films is the sol-gel method. Annealing process was carried out at 700°C for 1 hour. The manufacturing process of Ba0.9Sr0.1TiO3 and Ba0.4Sr0.6TiO3 materials in the form of capacitors on a glass substrate has been successfully carried out. The structures of Ba0.9Sr0.1TiO3 and Ba0.4Sr0.6TiO3 capacitors are glass/Al/BST/Al. This study aims to analyze the optical properties and electrical properties of BST thin films at different x compositions. Characterization of optical properties obtained by optical energy band gap values ​​which include absorbance, transmittance, refractive index values ​​and layer thickness uses the Tauc plot method. Characterization of electrical properties using impedance spectroscopy obtain capacitance values ​​and dielectric constants. The gap width of Ba0.9Sr0.1TiO3 thin film energy is 3.77 eV, while Ba0.4Sr0.6TiO3 is 3.43 eV, indicating that this material is a semiconductor material. The capacitance and dielectric constant values ​​at the frequency of 1 Hz for Ba0.9Sr0.1TiO3 thin films are 3.1 x 10-8 F and 0.034, while for Ba0.4Sr0.6TiO3 thin films are 4.2x10-8 F and 23.500. Keywords: BST thin films; Sol-Gel method; Energy band gap; Capacitance; dielectric   constant